DETECTION RESISTANCE GENES OF ROOT KNOT NEMATODE MI IN SOME OF PURE LINES OF TOMATO INDETERMINATE GROWTH - & Yassien, Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was included investigation of the resistance genes Mi which is responsible for the appearance of resistance feature in tomato against root knots Nematode Meloidogyne spp in 46 pure lines of tomato indeterminate growth, ten of tomato pure lines showed resistance to root knots nematode infection after 60 days of the inoculation by 5000 egg/ kg of soil . While 31 pure lines of tomato showed sensitivity for these nematode infection, which root knot  numbers had exceeded 100 knots. Then the genes has diagnosed by using the technology of molecular analysis the DNA of the purelines of sensitive and resistance tomato was isolated by the CTAB method then apply the indicators of Simple Sequence Repeat (SSR) DNA on the total DNA isolated from sensitive and resistant pure lines and using five primers connected with different locations of the resistance lines, two of them were designed by reasrcher and NCBI-Primer-Blast program (HSM1and HSM2) proved effective in the investigation of resistance genes Mi by production DNA bands, and three other primers (REX and C2S4 and Mi1-2) also proved their international effectiveness in the detection of resistance genes by production DNA bands for each pairs of them.